Three examples of Markovian functionals - Alimov, D. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Three examples are considered of the application of general limit theorems for Markov functionals: to the problem of the moment of exit of a Markov process from a subset of states; to the analysis of systems of mass service with relatively rapid service; to the asymptotics of the mean number of particles in a branching process in a Markov random medium.